HUBUNGAN DURASI KERJA DENGAN NYERI PUNGGUNG BAWAH PADA SOPIR TAXI ONLINE KOTA MAKASSAR - Andi Weri Sompa; Emy Andira (Jurnal Komunitas Kesehatan Masyarakat, 2020)
Background :Low back pain (LBP) is a non-specific condition that refers to complaints of acute or chronic pain and discomfort in the lumbosacral area. This condition is often found in the community as one of the musculoskeletal disorders, psychological disorders and as the consequences of wrong mobility. At present, as a result of rapid technological developments, innovations in public transportation increase online public transportation businesses that have an impact on social and economic conditions in Indonesia especially in Makassar. Increasing number of people work as online taxi driver makes LBP more frequent in public health services. Objective : This study wanted to show the relationship driving duration and LBP insidents on online taxi drivers in the city of Makassar.Methods: this study uses analytical observational method with cross sectional approach. We selected 53 respondents from online taxi driver. The datas were collected by the questionnaire and processed using the Chi-Square Test. Results: this study identified 83.3% of respondents with a driving duration more than 8 hours and as many as 16.7% who drives less than 8 hours had LBP complaints. The results of statistical tests using the Chi-Square Test obtained significance number 0.026 (p <0.05) which means that there is a linear relationship between driving duration and incidence of LBP on online taxi drivers in Makassar.